Estudo das propriedades de transporte de água e íons em tintas de acabamento à base de poliuretana alifática e poliuretana acrílica, novas e após envelhecimento sob radiação UV - Magaton, Marina (Universidade Federal de São Carlos, 2005)
The present work has as objective the comparative study between anticorrosive painting systems with two types of vehicle - aliphatic polyurethane and acrylic polyurethane - loaded with different concentrations of iron oxide of the red type (OFV) and the micaceous type (OFM), new and after aging under UV radiation. A set of fourteen different painting systems was studied, that vary between itself for the type used vehicle, as well as for the type and concentration of iron oxide added. Samples in form of free films had been submitted the assays of transport and sorption of water, ionic transport, Scanning Electronic Microscopy (MEV) and Atomic Force Microscopy (AFM). As general conclusion, the results show that for all the analyzed systems, the dispersion of pigments is below of the desired one, with formation of porous aggregate of the solids particles. This fact is evinced from the results of transport and water sorption, where an increase of the solubility of the systems with the increase of the pigment concentration was observed, and also, from images of the morphology of the samples, obtained from MEV analysis. The aged systems had presented permeabilities higher than those for the new films, in all the range of concentrations, being that in the case of the loaded systems with micaceous iron oxide the effect of the aging was small, in comparison to of the red iron oxide. The effect of the aging also can be observed through the images obtained from MEV analysis, for all the systems, as well as from images of MFA obtained for two specific systems. Assays of ionic transport had been carried through for four selected systems, and had corroborated with the results of transport and sorption of water. In this direction, four systems between those studied had been selected, that the carried through assays had presented better performances in all: aliphatic polyurethane with 5% of OFM and 35% of OFV, and acrylic polyurethane, with 5% and 35% of OFM.
Study of water and ion transport in painting systems based on polyurethane resins/iron oxide, before and after ageing under radiation UV
Keywords: Polímeros; Tintas; Propriedade de transporte; Compósitos poliméricos; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::POLIMEROS